Clinical Profile and Prevalence of Obstructive Sleep Apnea Syndrome in a Tertiary Care Hospital - Pokharel, Monika; Sapkota, Bikash; Prasad Pangeni, Raju (Birat Journal of Health Sciences, 2025)
Background : Obstructive sleep apnea syndrome is characterized by recurrent collapse of the upper airway during sleep associated with recurrent oxygen desaturation and sleep arousal . It is an undiagnosed public health problem with harmful implications . Objective : To find the correlation between risk factors and severity of obstructive sleep apnea . Methodology: Prospective and analytical study conducted among 61 participants in the Department of Otorhinolaryngology and Head and Neck Surgery, Dhulikhel Hospital. A detailed history and evaluation of the nose, oral cavity, oropharynx and larynx was performed The Epworth sleepiness score was filled .The body mass index was calculated. Overnight polysomnography was performed. Participants were classified as primary snoring, mild, moderate or severe obstructive sleep apnea groups. The relationship of the Apnea hypopnea index was analyzed with the body mass index and the Epworth sleepiness score. Results: Of the 61 participants,all had excessive daytime sleepiness .60(98.4%) complained of snoring and 46 (75.4%) complained of frequent awakening. Primary snoring was observed in 11(18.03%) patients, 9(14.75%) had mild , 16(26.22%) had moderate, while 25(40.98%) patients had severe obstructive sleep apnea .Significant association ( p <.001) was observed between AHI and BMI and Epworth sleepiness score and severity in different groups. Conclusion: Obstructive sleep apnea is often neglected as snoring. Patients with excessive daytime sleepiness, multiple apneic spells, high body mass index and Epworth sleepiness score should raise a clinical suspicion of obstructive sleep apnea and should undergo an overnight sleep study for diagnosis and early intervention.